Low-dose CT screening can reduce cancer mortality: A meta-analysis - Tang,Xue (2019)
SUMMARY OBJECTIVE Lung cancer is the leading cause of cancer-related death. To reduce lung cancer mortality and detect lung cancer in early stages, low dose CT screening is required. A meta-analysis was conducted to verify whether screening could reduce lung cancer mortality and to determine the optimal screening program. METHODS We searched PubMed, Web of Science, Cochrane library, ScienceDirect, and relevant Chinese databases. Randomized controlled trial studies with participants that were smokers older than 49 years (smoking >15 years or quit smoking 10 or 15 years ago) were included. RESULTS Nine RCT studies met the criteria. LDCT screening could find more lung cancer cases (RR=1.58, 95%CI=1.25-1.99, P<0.001) and more stage I lung cancers (RR=3.45, 95%CI=2.08-5.72, P<0.001) compared to chest-X ray or the no screening group. This indicated a statistically significant reduction in lung-cancer-specific mortality (RR=0.84, 95%CI=0.75-0.95, P=0.004), but without a statistically reduction in mortality due to all causes (RR=1.26, 95%CI=0.89-1.78, P=0.193). Annually, LDCT screening was sensitive in finding more lung cancers. CONCLUSIONS Low-dose CT screening is effective in finding more lung cancer cases and decreasing the deaths from lung cancer. Annual low-dose CT screening may be better than a biennial screening to detect more early-stage lung cancer cases.